Effects of Increased Transparency on Political Divides and MP Behavior: Evidence from Televised Question Hours in the Finnish Parliament - Nieminen Jeremias; Simola Salla; Tukiainen Janne (Wiley (Commercial Publisher), 2025)
We study the effects of increasing the transparency of parliamentary speeches on polarization and other types of MP behavior. We utilize the 1989 introduction of TV broadcasting to the Finnish government's parliamentary question hours held on the first Thursday of every month. By contrast, the question hours held on other Thursdays of the month were not televised until 2007, allowing us to use difference-in-differences design. We find a positive effect on government–opposition divides, but no evidence that the TV broadcasting of question hours would affect left–right polarization, differences between individual parties, or within-party group differences. We also observe an increase in attendance and a negative effect on the number of speeches, but no effects on topics discussed, speech length nor interruptions. Our results suggest there is no trade-off between increased transparency and left–right polarization. However, the presence of TV cameras can fuel other political divides and increase politicians’ effort.